2013
DOI: 10.5551/jat.17608
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus Aspiration Therapy and Coronary Thrombus Components in Patients with Acute ST-Elevation Myocardial Infarction

Abstract: Inflammation and oxidative stress play key roles in atherosclerotic plaque instability, and plaque rupture/erosion and subsequent thrombus formation constitute the principal mechanisms of total vessel occlusion and acute ST-elevation myocardial infarction (STEMI). Plaque disruption triggers the formation of initial platelet aggregates that grow in association with an increase in fibrin formation, leading to persistent coronary flow obstruction and blood coagulation. The fibrin network may trap large numbers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 121 publications
(120 reference statements)
2
24
0
Order By: Relevance
“…In STEMI patients presenting later that 6 h from symptom onset, insignificantly shorter clotting time, stiffer clot and longer clot lysis time were noted [8]. Similar results on coronary thrombus composition were obtained using histochemical techniques [9,10] or magnetic resonance imaging [11]. It has also been reported that the ruptured plaque is more prone to initiate the fibrin-rich thrombus formation as opposed to the eroded plaque [12].…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…In STEMI patients presenting later that 6 h from symptom onset, insignificantly shorter clotting time, stiffer clot and longer clot lysis time were noted [8]. Similar results on coronary thrombus composition were obtained using histochemical techniques [9,10] or magnetic resonance imaging [11]. It has also been reported that the ruptured plaque is more prone to initiate the fibrin-rich thrombus formation as opposed to the eroded plaque [12].…”
Section: Introductionsupporting
confidence: 66%
“…It has also been reported that the ruptured plaque is more prone to initiate the fibrin-rich thrombus formation as opposed to the eroded plaque [12]. Moreover, serum myeloperoxidase (MPO) derived from activated neutrophils and monocytes is elevated in ACS and MPO-positive neutrophils represent a larger component of intracoronary thrombi in the ACS patients with eroded plaques [9,13,14].…”
Section: Introductionmentioning
confidence: 96%
“…These results can be explained by the high local concentrations of eptifibatide achieved in IC administration in comparison to the IV route. Similar to abciximab and tirofiban, eptifibatide is a GPI that blocks the final common pathway of platelet aggregation by binding to platelet GP b/ a receptors, which bind to fibrinogen and other adhesive proteins that crosslink adjacent platelets 4,[33][34][35] . It also has dose-dependent antiplatelet, dethrombotic, and anti-inflammatory features [6][7][8][34][35][36] .…”
Section: Fig 2 Post-pci Timi Flow Gradementioning
confidence: 99%
“…Similar to abciximab and tirofiban, eptifibatide is a GPI that blocks the final common pathway of platelet aggregation by binding to platelet GP b/ a receptors, which bind to fibrinogen and other adhesive proteins that crosslink adjacent platelets 4,[33][34][35] . It also has dose-dependent antiplatelet, dethrombotic, and anti-inflammatory features [6][7][8][34][35][36] . Because they compete with fibrinogen in binding to the platelet GP b/ a receptor, high localized concentrations of the drug may enable the dissociation of bound fibrinogen and dissolve the formed thrombus 6,[36][37][38] .…”
Section: Fig 2 Post-pci Timi Flow Gradementioning
confidence: 99%
“…The use of intracoronary imaging modalities such as Intra Vascular Ultra Sound (IVUS) and Optical Coherence Tomography (OCT) is very helpful as guiding the expansion and apposition of the stent to be more adequate (Buchanan et al 2012). Also look for mechanical predisposing factors underlying ST (Yunoki et al 2012).…”
Section: Preventing Stent Thrombosismentioning
confidence: 99%